Ethnomicological Study of Macrofungi in Sesaot Forest of West Lombok - Meilinda Pahriana Sulastri; Hasan Basri; Arista Suci Andini (Jurnal Penelitian Pendidikan IPA, 2024)
Communities living near forested areas play a crucial role in preserving forest biodiversity. Ethnomycological studies are an important first step in identifying the variety and potential of macrofungi used by people in a region. This study aims to document the use of macrofungi by the local community around Sesaot forest. The collection and identification of macrofungi samples were carried out using opportunistic sampling. Data on the use of macrofungi was obtained from semi-structured interviews with residents around Sesaot Forest. A total of 26 respondents from the Sesaot community participated in the survey. The people usually collected macrofungi for consumption and occasionally for medicinal purposes. The results identified 12 species of macrofungi from 10 families (Pezizaceae, Auriculariaceae, Sarcoscyphaceae, Gomphaaceaae, Pleurotaceae, Ganodermataceae, Psathyrellaceae, Polyporaceae, Agaricaceae, and Nidulariaceae) in Sesaot forest. Auricularia sp. and Pleurotus sp. were used as food, while Lignosus sp. was used as medicine by the local people in Sesaot.